Structural Decomposition of the Impact of World Oil Price Shock Economic Growtth In Indonesia - Fahmi Aziz (Journal of International Conference Proceedings, 2024)
The aim of this research is to determine the response of economic growth in Indonesia to shocks or variable shocks in world oil prices, gold prices, inflation, exchange rates and interest rates. This research uses time series data for 12 years (2010-2021) using the Vector Auto Regressive (VAR) method. The results show that based on the results of the Impulse Response Function (IRF) test, world oil price shocks responded positively to economic growth in the 2nd period, 5-6th period and 9-10th period, while the response was negative in the 3rd-4th period and the 2nd period. 7th-8th. Gold price shocks were responded positively by economic growth in periods 3-4 and 7-8, while the response was negative in periods 2, 5-6 and 9-10. Inflation shocks were responded positively by economic growth in periods 2, 4-5 and 8-9, while negative responses in periods 3, 6-7 and 10. Exchange rate shocks were responded positively by economic growth in periods 3- 4 and 7-8, while the response was negative in the 2, 5-6 and 9-10 periods. Interest rate shocks responded positively to economic growth in periods 2, 5-6 and 9, while negative responses in periods 3-4, 7-8 and 10. Based on the results of the Variance Decomposition test, oil prices contributed 4,886%, gold contributed 5,545%, inflation contributed 0.306%, interest rates contributed 1,197%, and the exchange rate was the variable that contributed the most, namely 6,396%.The aim of this research is to determine the response of economic growth in Indonesia to shocks or variable shocks in world oil prices, gold prices, inflation, exchange rates and interest rates. This research uses time series data for 12 years (2010-2021) using the Vector Auto Regressive (VAR) method. The results show that based on the results of the Impulse Response Function (IRF) test, world oil price shocks responded positively to economic growth in the 2nd period, 5-6th period and 9-10th period, while the response was negative in the 3rd-4th period and the 2nd period. 7th-8th. Gold price shocks were responded positively by economic growth in periods 3-4 and 7-8, while the response was negative in periods 2, 5-6 and 9-10. Inflation shocks were responded positively by economic growth in periods 2, 4-5 and 8-9, while negative responses in periods 3, 6-7 and 10. Exchange rate shocks were responded positively by economic growth in periods 3- 4 and 7-8, while the response was negative in the 2, 5-6 and 9-10 periods. Interest rate shocks responded positively to economic growth in periods 2, 5-6 and 9, while negative responses in periods 3-4, 7-8 and 10. Based on the results of the Variance Decomposition test, oil prices contributed 4,886%, gold contributed 5,545%, inflation contributed 0.306%, interest rates contributed 1,197%, and the exchange rate was the variable that contributed the most, namely 6,396%.